The Affordable Care Act Reduced Socioeconomic Disparities In Health Care Access - Griffith, Kevin (Health Aff (Millwood), 2017)
The United States has the largest socioeconomic disparities in health care access of any wealthy country. We assessed changes in these disparities in the United States under the Affordable Care Act (ACA). We used survey data for the period 2011–15 from the Behavioral Risk Factor Surveillance System to assess trends in insurance coverage, having a personal doctor, and avoiding medical care due to cost. All analyses were stratified by household income, education level, employment status, and home ownership status. Health care access for people in lower socioeconomic strata improved in both states that did expand eligibility for Medicaid under the ACA and states that did not. However, gains were larger in expansion states. The absolute gap in insurance coverage between people in households with annual incomes below $25,000 and those in households with incomes above $75,000 fell from 31 percent to 17 percent (a relative reduction of 46 percent) in expansion states and from 36 percent to 28 percent in nonexpansion states (a 23 percent reduction). This serves as evidence that socioeconomic disparities in health care access narrowed significantly under the ACA.